HBR's 10 must reads on teams (Boston, 2013)
Assemble and steer teams that get results. These ten essential Harvard Business Review articles will help you ramp up your team's performance, rally the troops and keep them accountable, fight constructively, and set goals everyone can agree on.
Keywords: Đội ngũ tại nơi làm việc,Teams in the workplace